2015
DOI: 10.15430/jcp.2015.20.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeting of ERKs/RSK2 Signaling Axis in Cancer Prevention

Abstract: RSK2 is a downstream signaling protein of ERK1 and ERK2 and plays a key role in physiological homeostasis. For this reason, RSK2 is a highly conserved protein among the p90RSK family members. In its location in the signaling pathway, RSK2 is a kinase just upstream of transcription and epigenetic factors, and a few kinases involved in cell cycle regulation and protein synthesis. Moreover, activation of RSK2 by growth factors is directly involved in cell proliferation, anchorage-independent cell transformation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
(94 reference statements)
0
9
1
Order By: Relevance
“…Kaempferol also inhibited cell proliferation of cancer cells. 43 The measurement of cell proliferation assay in this study also contradicted previous studies. These results indicated that the differences depended on the loading method of kaempferol.…”
Section: Discussioncontrasting
confidence: 88%
“…Kaempferol also inhibited cell proliferation of cancer cells. 43 The measurement of cell proliferation assay in this study also contradicted previous studies. These results indicated that the differences depended on the loading method of kaempferol.…”
Section: Discussioncontrasting
confidence: 88%
“…ERK2 and CRAF isoforms are implicated in the well-established ERK-RAF NFB, known to regulate ERK dynamics (Santos et al 2007; Ryu et al 2015; Blum et al 2019), and to enable consistent ERK dynamics under MEK or ERK perturbations (Fritsche-Guenther et al 2011; Sturm et al 2010). RSK2 encodes the p90 ribosomal S6 kinase 2 protein, an ERK substrate regulating survival and proliferation (Cargnello and Roux 2011; Yoo et al 2015). RSK2 is also known to be involved in an ERK-induced NFB targeting SOS (Douville and Downward 1997; Saha et al 2012; Lake et al 2016), whose significance in the regulation of ERK dynamics has been less well studied.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Cho et al discovered that RPS6KA3, which is activated by its upstream kinases, ERK1 and ERK2, plays a central role in human skin cancer development [35]. It was also reported that RPS6KA3 is activated by different growth factors that are closely related to cell proliferation, anchorage-independent cell transformation, and cancer development [36]. In the present study, although RPS6KAS was not associated with clinicopathologic characteristics of sporadic MTC, it was significantly upregulated in MTC tumorous tissues and could be used to distinguish sporadic MTC tumorous tissues from the paired normal thyroid tissues; the AUC of RPS6KAS was similar to that of the clinical biomarker CALCA and CEACAM5.…”
Section: Discussionmentioning
confidence: 99%